#### Question

If A = B = 60°. Verify `tan (A - B) = (tan A - tan B)/(1 + tan tan B)`

#### Solution

Given:

A = B = 60° ......(1)

To verify:

`tan (A - B) = (tan A - tanB)/(1 + tan Atan B)` ......(2)

Now consider LHS of the expression to be verified in equation (2)

Therefore.

`tan (A - B) = tan (B - B)`

= tan 0

= 0

Now consider RHS of the expression to be verified in equation (2)

Therefore

Now by substituting the value of *A* and *B* from equation (1) in the above expression

We get,

`(tan A - tan B)/(1 + tanA tan B) = (tan B - tan B)/(1 + tanB tan B)`

`= 0/(1 + tan^2 B)`

= 0

Hence it is verified that,

`tan (A - B) = (tan A - tan B)/(1 + tan tan B)`

Is there an error in this question or solution?

#### APPEARS IN

Solution If a = B = 60°. Verify Tan (A - B) = (Tan a - Tan B)/(1 + Tan Tan B) Concept: Trigonometric Ratios of an Acute Angle of a Right-angled Triangle.